PF-27 Incidence of Feline Dermatophytosis at Dramaga, Bogor in 2013-2018 - Agustin Indrawati; Titiek Sunartati; Handina Rakhmawati (Hemera Zoa, 2018)
Indonesia has a tropical climate and high humidity that give a high prevalence for fungal infections in cat skin such as Feline dermatophytosis (ringworm). Dermatophytosis is the most common fungal infection of cats and one of the most important infectious skin diseases in this species. It may be transmitted to other animal species and also contangious nature, zoonotic potential (Moriello, 2014). Feline dermatophytosis cases are caused by genera Microsporum, Trichophyton, and Epidermophyton. All of these agents produce proteolytic and keratolytic enzymes that enable them to utilize keratin as the sole source of nutrition after colonization of the dead, keratinized portion of epidermal tissue (mostly stratum corneum and hairs, sometimes nails) (Mattei et al., 2014). The aim of this study are to identified and evaluate the kind of fungal that can cause feline dermatofitosis in Dramaga in 2013 until 2018.